Strengthening Indonesia's Position as an Archipelagic States through Coordinative Law Enforcement the Archipelagic Sealanes Passage on the Alki - ‎ , Irawati; Effendi, Dedy; Chotidjah, Nurul (KnE Social Sciences, 2024)
This paper examines law enforcement in an effort to maintain security and order in Indonesian archipelagic waters. Indonesia has accommodated the right of archipelagic sea lanes passage by establishing three archipelagic sea lanes. In implementing the right of Indonesian archipelagic sea lanes passage, many violations have occurred both by ships and foreign aircraft, there are still many criminal acts and violations of sovereignty both at sea and in the air. The research aims to find the concept of coordinating law enforcement for the right to sea lanes passage in ALKI. The method to be used in this research is normative juridical. The specification of the research used is analytical prescriptive. Based on the results of the study it is known that law enforcement agencies have overlapping powers. BAKAMLA has very broad powers including authority as the TNI and authority as the Police. Coordinative law enforcement can be realized through the distribution of authority among law enforcers in a proportional and coordinated manner under one command. Criminal acts at sea will be the domain of all law enforcers but in coordination of the Water Police. While acts of violation of sovereignty committed by foreign ships or aircraft will fall under the authority of the Indonesian Navy and Indonesian Air Force as Coordinators. Keywords: sea lanes passage, law enforcement, coordinative, territorial jurisdiction